Description of Treponema azotonutricium sp. nov. and Treponema primitia sp. nov., the First Spirochetes Isolated from Termite Guts - Graber, Joseph R. (American Society for Microbiology, 2004)
Long after their original discovery, termite gut spirochetes were recently isolated in pure culture for the first time. They revealed metabolic capabilities hitherto unknown in the Spirochaetes division of the Bacteria, i.e., H(2) plus CO(2) acetogenesis (J. R. Leadbetter, T. M. Schmidt, J. R. Graber, and J. A. Breznak, Science 283:686-689, 1999) and dinitrogen fixation (T. G. Lilburn, K. S. Kim, N. E. Ostrom, K. R. Byzek, J. R. Leadbetter, and J. A. Breznak, Science 292:2495-2498, 2001). However, application of specific epithets to the strains isolated (Treponema strains ZAS-1, ZAS-2, and ZAS-9) was postponed pending a more complete characterization of their phenotypic properties. Here we describe the major properties of strain ZAS-9, which is readily distinguished from strains ZAS-1 and ZAS-2 by its shorter mean cell wavelength or body pitch (1.1 versus 2.3 μm), by its nonhomoacetogenic fermentation of carbohydrates to acetate, ethanol, H(2), and CO(2), and by 7 to 8% dissimilarity between its 16S rRNA sequence and those of ZAS-1 and ZAS-2. Strain ZAS-9 is proposed as the type strain of the new species, Treponema azotonutricium. Strains ZAS-1 and ZAS-2, which are H(2)-consuming, CO(2)-reducing homoacetogens, are proposed here to be two strains of the new species Treponema primitia. Apart from the salient differences mentioned above, the genomes of all three strains were similar in size (3,461 to 3,901 kb), in G+C content (50.0 to 51.0 mol%), and in possession of 2 copies of the gene encoding 16S rRNA (rrs). For comparison, the genome of the free-living spirochete Spirochaeta aurantia strain J1 was analyzed by the same methods and found to have a size of 3,719 kb, to contain 65.6 mol% G+C, and also to possess 2 copies of the rrs gene.